Grain quality-based selection and QTL mapping in a Ciherang-subl backcross population. Issue 1 (April 2020) - Pramudyawardani, Estria F; Aswidinnoor, H; Purwoko, B S; Suwarno, W B; Verdeprado, H; Islam, M R; Collard, B C Y
Abstract: Ciherang has been a dominant variety in Indonesia for almost 2 decades and is considered to be a premium rice in Indonesia. Despite the importance of this variety, limited information is available regarding the genetic control of grain quality traits. A backcross population (Ciherang-Sub1*2/IRRI148) was developed for mapping a range of traits. This study was performed to select promising families with similar rice grain quality as Ciherang-Sub1 and to identify QTLs associated with grain quality from Ciherang-Sub1. Nine quality traits (chalkiness; seed length, width, and shape; brown rice, milled rice percentage, head rice recovery percentage, amylose content) and 3 complementary data (gelatinization temperature, gel consistency, milling potential degree) were measured at the IRRI Grain quality and nutrition centre. Selection using two clustering methods identified 32 promising families which had similar grain quality as Ciherang-Sub1. Using the ICIM QTL mapping method, 12 grain quality QTLs were identified. Eight of those were newly identified QTLs (qSL2.1, qSL8.1, qSWdl.1, qBrPl.1, qBrP3.1, qBrP9.1, qMP2.1 and qGT6.2). Large effect QTLs were identified for the seed length (R 2 = 63.61%), seed shape (R 2 = 41.29), and gelatinization temperature (R 2 = 41.52%). Both parents contributed alleles that affected quality, where 2 QTLs from seed length and width increased seed shape. The promising families and QTLs identified in this study could be useful for enhancing rice grain quality using molecular marker assisted breeding and developing new rice varieties with premium quality in the future.